Efficiency in provision of public dental services in Norway - Grytten J, Rongen G: (Blackwell Synergy, 2000)
The paper examines productivity in the provision of public dental services in Norway. The main responsibility of the public dental services is to provide care for all children up to 18 years of age. Most dental care is provided by public dental officers. Productivity was measured by estimating a stochastic production frontier from input and output data from the public dental service in Key words: dentists; efficiency; stochastic production frontier Norway.